The military as an economic actor soldiers in business - Brommelhörster, Jorn; Paes, Wolf-Christian (Palgrave Macmillan, 2003)
Armed forces across the globe engage in economic activities both in times of war and peace. This book provides a critical analysis of this phenomenon, comparing experiences with "military business" from four continents (Asia, Africa, Europe and Latin America). Taking an interdisciplinary approach, the volume shows the implications of "military business" for civil-military relations, good governance and international development policies.